Spot-check observations for assessing hygiene practices: review of experience and implications for programs - Ruel, Marie T.; Arimond, Mary (Springer, 2002)
Structured observations, considered to be the method of choice for assessing hygiene practices, are time-consuming and expensive and are subject o reactivity (households modifying their behaviours in he presence of an observer).Hygiene practices also vary from day to day. Spot-checks, an alternative approach for observation, have recently gained increased popularity. In this approach, a list of predetermined conditions is observed at one point in time during a home visit. This paper reviewed experience with spot-checks for measuring hygiene practices and discussed strengths and weaknesses of he approach and its potential usefulness to hose undertaking programmes.Review of seven studies carried out in various contexts confirmed that spot-checks are a promising alternative to structured observations, because these are less intrusive, less time-consuming,more economical, and less reactive..." -- Authors' Abstract